2019
DOI: 10.1038/s41598-019-51837-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteins and microRNAs are differentially expressed in tear fluid from patients with Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is characterized by a progressive loss of neurons and cognitive functions. Therefore, early diagnosis of AD is critical. The development of practical and non-invasive diagnostic tests for AD remains, however, an unmet need. In the present proof-of-concept study we investigated tear fluid as a novel source of disease-specific protein and microRNA-based biomarkers for AD development using samples from patients with mild cognitive impairment (MCI) and AD. Tear protein content was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 64 publications
1
90
0
Order By: Relevance
“…Another study suggested the discriminatory power of tear T-tau and Aβ 42 , as their levels increased in AD patients [ 186 ]. Additionally, total microRNA abundance was also found at increased levels in AD patients, with microRNA-200b-5p as the most promising AD biomarker [ 183 , 187 ].…”
Section: Emerging Body Fluid Biomarkersmentioning
confidence: 99%
“…Another study suggested the discriminatory power of tear T-tau and Aβ 42 , as their levels increased in AD patients [ 186 ]. Additionally, total microRNA abundance was also found at increased levels in AD patients, with microRNA-200b-5p as the most promising AD biomarker [ 183 , 187 ].…”
Section: Emerging Body Fluid Biomarkersmentioning
confidence: 99%
“…Furthermore, the isolation of tears for the detection of possible AD biomarkers may provide an even less invasive approach. In this regard, a recent study has corroborated the presence of specific miRNAs in the tears of AD patients [ 49 ]. This finding is, therefore, a good starting for the search of potential AD markers in this fluid.…”
Section: Resultsmentioning
confidence: 90%
“…Kallo et al (10) used mass spectrometry to compare ten priorly selected proteins in tear uid samples from AD patients versus controls and observed differences for lipocalin-1, lactotransferrin, extracellular glycoprotein lacritin, lysozyme-C, prolactin inducible protein and dermcidin. Kenny et al (11) used mass spectrometry on tear uid from AD patients versus controls. They identi ed a panel of 12 proteins that were differentially expressed in tear uid of AD patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Kallo et al (10) identi ed differences in the total tear protein composition in AD patients. Recently, Kenny et al (11) performed differential expression of tear uid from AD patients and controls by mass spectrometry. Based on these studies, it is reasonable to assume presence of amyloid-beta and tau in tear uid.…”
Section: Introductionmentioning
confidence: 99%